PENGUKURAN PARTIKEL DI CLEANROOM TFME POLITEKNIK NEGERI BATAM MENGGUNAKAN STANDAR ISO 14644-1 - Aditya Gautama; Budiana Budiana (Politeknik Negeri Batam, 2020)
Electronics Tecnology is currently developing very rapidly. Computational capabilities that continue to increase are accompanied by a decrease in the size of the electronic components used on a chip or IC (Integrated Circuit). The size of the components that have reached nanometers makes the components very sensitive to impurities in the form of particles. A special fabrication place in the form of a cleanroom is needed so that the number of impurity particles can be controlled and the damage caused by impurity particles on the product can be reduced. One of the standards used to classify a cleanroom and measure the particles in it is ISO 14644-1. In this study, particle measurements were carried out in accordance with ISO 14644-1 standards to measure the number of particles in the TFME cleanroom. The measurement results classify the cleanroom in TFME into ISO Class 7. This is consistent with the initial TFME cleanroom design, meaning that the particle filtration system is still in a good condition.